Peran Ganda Wanita Teori Konflik Pekerjaan-Keluarga: Sebuah Kajian Kritis - Harsuti Harsuti; fatwa Zuhaena (FEB UNWIKU PURWOKERTO, 2021)
In today's modern era, a woman is not only a housewife. Today's women have started to enter the public sector where they have to work. Armed with the skills and education currently available, women have the courage to work outside the home. This creates a dual role that can be said to be more than two roles for women who are daily workers. The role adopted by women workers is the role of being a mother for their children and being a good wife for her husband. In balancing roles, a woman finds it difficult and has many obstacles. A woman who cannot balance her roles will have an impact on her family and work. But the most important thing is the impact on his family. A woman has an important obligation to take care of the family household. If it has a negative impact it will disrupt family life, and have a significant impact on husbands and children. The issue of dual roles is also experienced by female K3L workers at Padjadjaran University. They are obligated to fulfill their roles as a mother and a wife and become K3L workers at the same time. Keywords: Multiple Roles, Conflict Theory, Women's Labor